A review of the relationship between CSR and the internal business process - Al-Hosaini, Fahmi Fadhl (2015)
Most of the previous investigations on organisational performance were directed towards the financial status at the expense of other social requirements, particularly with respect to firms’ operating environments. In addition, such studies were geared towards better understanding of the influence of Corporate Social Responsibility (CSR) on Organizational Performance without adequate consideration for those non-financial factors, such as the Internal Business Perspective (IBP) that also affect the success of organizational strategic goals. The incorporation of CSR into organizational processes in driving home their strategic management success has been proven to be linked. In this paper, we review the inter relationship between CSR and IBP, and identify major themes from the literature. This study therefore justifies the need for an empirical study to further examine the interrelationships among these variables so as to provide better understanding of the influence of the CSR on the IBP.